PAGELARAN SEBAGAI SALAH SATU BAURAN HUMAS LKB (LEMBAGA KEBUDAYAAN BETAWI) DALAM MELESTARIKAN KESENIAN LENONG BETAWI - Asriyani Sagiyanto (Cakrawala - Jurnal Humaniora, 2015)
Along with the times and the modernization of the capital Jakarta, influence on the existence of Betawi art and culture. The influence evident from the many people who are less supportive Betawi culture itself, among others, they prefer to watch the show and art of modern culture such as films or bands compared with the traditional arts such as lenong, gambang kromong , masks and others.Lenong a Betawi arts, theater or one of the Betawi people taking the stories of heroism and criminal as its theme. With Thus LKB which is an institution engaged in the preservation and Betawi arts development, should pay more attention to the art of Betawi culture lenong particular art, by holding performances. It aims to introduce and promote the cultural arts Betawi people in Jakarta and at the same time to develop and preserve Betawi arts, especially the arts lenong high value, which is now in the midst of modern art and culture.The purpose of this study was to find out that the show is a mix of public relations or media LKB, LKB to preserve the arts lenong Betawi . In addition , this study also aims to determine the mix of other Public relations conducted by the LKB preserve Betawi arts culture, particularly lenong Betawi arts.The method used in this study is a research method descriptive qualitative approach. Data used in the study form of primary data, through interviews with key informants and informants andsecondary data obtained from the literature study and observation . The results showed that the role of performance as one of the mix public relations LKB lenong in preserving Betawi arts , has been running with although its function is not optimal. That is in addition to preserving and developing a culture of Betawi art, especially Betawi arts lenong . performances also aims to introduce and promote the art and culture of Betawi to the people of Jakarta and the Indonesian people in general.Keywords: Culture of Betawi, Mix of Public Relations, Perfomance